Three cases of endoscopic resection for synchronous early colon cancers after self-expandable metallic stent placement for obstructive colon cancer - Moroi, Rintaro; Endo, Katsuya; Ichikawa, Ryo; Takahashi, So; Shiroki, Takeharu; Shinkai, Hirohiko; Ishiyama, Fumitake; Kayaba, Shoichi (Endoscopy International Open, 2016)
Background and study aims: The feasibility of endoscopic resection for synchronous early colon cancer after placement of self-expandable metallic stents (SEMS) for malignant colorectal obstruction is unknown. Herein we evaluated 3 cases of endoscopic resection for synchronous early colorectal cancers after SEMS placement. Patient 1 was an 82-year-old man with obstructive sigmoid colon cancer. We curatively treated the synchronous descending colon cancer with endoscopic submucosal dissection (ESD) and the rectal cancer with endoscopic mucosal resection (EMR) after SEMS placement. This is the first reported case of a successful ESD for synchronous early colon cancer via the use of a colonic stent. Patient 2 was an 81-year-old man with obstructive ascending colon cancer. We resected the synchronous transverse colon cancer via ESD. Histologic findings indicated that the carcinoma cells had invaded the submucosal layer. Therefore, we immediately performed expanded right-hemicolectomy. Patient 3 was an 81-year-old man with obstructive sigmoid colon cancer. We curatively treated the synchronous transverse colon cancer with EMR after SEMS placement. There were no complications associated with the endoscopic treatments in any of the cases. Our results indicate that preoperative endoscopic resection combined with the ESD technique for synchronous colorectal cancer after SEMS placement could be effective as a surgical strategy for patients with malignant colorectal obstruction.